Synthetic Fertilizer Increases Denitrifier Abundance and Depletes Subsoil Total N in a Long-Term Fertilization Experiment - Wang, Ying; Ji, Hongfei; Wang, Rui; Hu, Yaxian; Guo, Shengli (Frontiers in Microbiology, 2020)
Chronic synthetic nitrogen (N) application can result in a significant accumulation of nitrate in the subsoil, which could alter subsoil N cycle and subsequently affect subsoil N levels. To understand how elemental interactions affect the cycle and storage of subsoil N, we examined the soils receiving no fertilizer control (CK), 30-year applications of synthetic fertilizer (CF,) and CF plus organic manure (CF+OM). The N cycling microbial groups and activity were investigated through analyzing abundance of bacteria, nitrifiers and denitrifiers, potential nitrification (PNA) and denitrification (DEA) rates in the topsoil (0-20 cm) and subsoil depths (20-80 cm). Compared with the CK, the CF application increased subsoil nitrate but reduced or did not change subsoil microbial biomass N and total N. Corresponding to the increased nitrate, the abundances of denitrifiers increased in the CF subsoils. By contrast, the abundances of nitrifers increased in the CF topsoil. Significant correlation between the abundances of nitrifiers and soil PNA was found in the topsoil while significant correlation was also found in subsoil between the abundances of nirS- and/or nirK- type denitrifiers and DEA. These results suggest that the depleted or less changed subsoil total N by CF application might be partly related to the enriched denitrifiers groups and the related potential activity. The contrasting responses of nitrifiers and denitrifiers in the CF subsoil indicate a decoupling of both processes. Our findings highlight that the leached nitrate by synthetic fertilizer addition not only occurs as an environmental risk causing groundwater contamination, but may also alter the subsoil N cycle through the denitrifier groups.